A Medical Informatics Perspective on Clinical Decision Support Systems - Bouaud, J.; Lamy, J.-B. (Yearbook of Medical Informatics, 2013)
Objective: To summarize excellent research and to select best papers published in 2012 in the field of computer-based decision support in healthcare.Methods: A bibliographic search focused on clinical decision support systems (CDSSs) and computer provider order entry was performed, followed by a double-blind literature review.Results: The review process yielded six papers, illustrating various aspects of clinical decision support. The first paper is a systematic review of CDSS intervention trials in real settings, and considers different types of possible outcomes. It emphasizes the heterogeneity of studies and confirms that CDSSs can improve process measures but that evidence lacks for other types of outcomes, especially clinical or economic. Four other papers tackle the safety of drug prescribing and show that CDSSs can be efficient in reducing prescription errors. The sixth paper exemplifies the growing role of ontological resources which can be used for several applications including decision support.Conclusions: CDSS research has to be continuously developed and assessed. The wide variety of systems and of interventions limits the understanding of factors of success of CDSS implementations. A standardization in the characterization of CDSSs and of intervention trial reporting will help to overcome this obstacle.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; decision support systems